Design of a two seats light sport aircraft. (January 2019) - Omar, Z
Abstract: Although flying machines have made their tremendous technological advancement since the first successfully flight of heavier-than-air aircraft, its benefits to the greater community are still belittled. One of the reasons for these drawbacks is because the relatively high cost needed to to fly on the typical light aircraft. A smaller and lighter plane, widely known as Light Sport Aircraft (LSA) which has the potential to attract more people of the greater community to actively participate in flying the LSA for recreational, business trip or other personal purposes. In this paper, we propose a new LSA design with some simple, yet importance analysis required in the aircraft conceptual design stage.